2013
DOI: 10.1159/000351822
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nonsense Mutation in Exon 1 of <b><i>HSD17B3</i></b> Gene in an Egyptian 46,XY Adult Female Presenting with Primary Amenorrhea

Abstract: 17-β-Hydroxysteroid dehydrogenase type 3 deficiency is a rare autosomal recessive cause of 46,XY disorder of sex development. Worldwide, about 30 mutations in the hydroxysteroid (17-beta) dehydrogenase 3 (HSD17B3) gene have been reported, involving all exons except exon 1. Herein, we investigated an Egyptian female with 46,XY karyotype and low testosterone/Δ4-androstenedione ratio. Genomic DNA was extracted from blood samples, and then, direct DNA sequencing of HSD17B3 gene was performed. The patient had a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…We have previously reported a nonsense mutation in exon 1 in a 46,XY patient with primary amenorrhea [Hassan et al, 2013]. Adding the reported mutation to those in the current study revealed that 50% of the mutation carrying alleles (11/22 alleles) among the studied probands were novel ( fig.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…We have previously reported a nonsense mutation in exon 1 in a 46,XY patient with primary amenorrhea [Hassan et al, 2013]. Adding the reported mutation to those in the current study revealed that 50% of the mutation carrying alleles (11/22 alleles) among the studied probands were novel ( fig.…”
Section: Discussionsupporting
confidence: 51%
“…table 1). These include 4 nonsense mutations and 4 exonic deletions that result in premature stop codons [George et al, 2010;Alikasifoglu et al, 2012;Ben Rhouma et al, 2013;Hassan et al, 2013;Al-Sinani et al, 2015;Sagsak et al, 2015;Tuhan et al, 2015]. Also, a large duplication spanning from intron 2 to intron 10 was reported twice, both in a heterozygous pattern [Neocleous et al, 2012;Massanyi et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-eight articles reported one or more patients with HSD17B3 mutations ( Supplemental Table S1 ) [ 1 , 3 , 4 , 5 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
Section: Resultsmentioning
confidence: 99%